FIRM’S UNETHICAL BEHAVIOR IN INDONESIA: A PRELIMINARY STUDY USING NEGATIVE CASE ANALYSIS - Kresno Agus Hendarto; Iva Ariani (EKUITAS (Jurnal Ekonomi dan Keuangan), 2012)
In Indonesia now, media, both printed and television pays attention to Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) more than even before. However, the reality of business life is quite different from the image presented in the media. This study tries to describe unethical behaviour of firms in Indonesia that documented in printed media and classify them to be measured qualitatively. News of CSR issued from January 2005 to December 2007 was gathered and analyzed using qualitative content analysis method with negative or deviant case analysis. Negative case analysis is an analysis to see something of the opposite. It used because of ethical relativism (ethical beliefs differ from one society to another society, even among people with one another). The results show that there are some unethical behaviors of firms. These unethical behaviors can be classified into unethical behavior directed internally to firm and those directed externally to Governments and society at large.